Rapid and accurate synthesis of TALE genes from synthetic oligonucleotides - Wang, Fenghua (BioTechniques, 2016)
Custom synthesis of transcription activator-like effector (TALE) genes has relied upon plasmid libraries of pre-fabricated TALE-repeat monomers or oligomers. Here we describe a novel synthesis method that directly incorporates annealed synthetic oligonucleotides into the TALE-repeat units. Our approach utilizes iterative sets of oligonucleotides and a translational frame check strategy to ensure the high efficiency and accuracy of TALE-gene synthesis. TALE arrays of more than 20 repeats can be constructed, and the majority of the synthesized constructs have perfect sequences. In addition, this novel oligonucleotide-based method can readily accommodate design changes to the TALE repeats. We demonstrated an increased gene targeting efficiency against a genomic site containing a potentially methylated cytosine by incorporating non-conventional repeat variable di-residue (RVD) sequences